Glanders - Vincent, Samuel Robert (My University, 1894)
Introduction: The disease known as glanders is a malignant infectious germ disease to which the genus Equus, the horse, the mule, and the ass is most susceptible. It is a specific disease of vegetable origin which is quite peculiar in its form of presentation and in the length of time for it to incubate. Farcy is a name which is often used as one stage of glanders or a disease that is apt to develop into glanders. Let all such erroneous ideas be abandoned at the outset. They are one and identical. The only difference being in the form of presentation. Glanders is a term applied to this in whatever form it may appear, while farcy is generally applied to the disease when its principal manifestation is an outbreak of the lesions on the exterior of the body; but even when it does only show upon the skin there are always internal lesions although they are not apparent.
Citation: Vincent, Samuel Robert. Glanders. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: Disease; Horse; Equus; Glanders; Sickness; Veterinary medicine; Equine; Theses; Manuscripts (documents)